Rutin Inhibits Cardiac Apoptosis and Prevents Sepsis-Induced Cardiomyopathy - Meng, Xiang-Long; Yu, Mu-Ming; Liu, Yan-Cun; Gao, Yu-Lei; Chen, Xin-Sen; Shou, Song-Tao; Chai, Yan-Fen (Frontiers in Physiology, 2022)
Rutin is a flavanol-type polyphenol that consists of flavanol quercetin and the disaccharide rutinose, which has been reported to exert various biological effects such as antioxidant and anti-inflammatory activities. It is not clear whether rutin has a protective effect on sepsis-induced cardiomyopathy (SIC). In this study, we used male C57BL/6 mice and cecal ligation and puncture (CLP) surgery to establish the model of SIC. Rutin was precautionarily treated (50, 100, 200 mg/kg per day, 7 days) before CLP. The results showed that rutin pretreatment (100, 200 mg/kg per day, 7 days) reduced the mortality of murine sepsis. We chose the 100 mg/kg dose for further studies. Mice were pretreatment with rutin (100 mg/kg per day, 7 days) before subjected to CLP, and myocardial tissue and blood samples were collected 24 h after CLP. Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and cTNT decreased, while interleukin-10 (IL-10) increased with rutin pretreatment. The cardiomyocytes apoptosis and mitochondrial dysfunction were also alleviated with rutin pretreatment. In conclusion, this study confirmed the efficacy of rutin-enriched diet in the prophylaxis of cardiac apoptosis and cardiac injury induced by CLP in mouse model. It provides a potential new approach on SIC prophylaxis in sepsis.